Beyond Financial Literacy CP 020 2026 : Perencanaan & Evaluasi PAI Ekonomi Syariah Menuju Sustainable Islamic Education & SDGs 2030 - Dwi Meutia Hasni; Dina Marni; Rafika Nisa; Erni Suyani; Andri Rivai (STIKes Ibnu Sina Ajibarang, 2026)
The implementation of the Decree of the Head of the Basic and Secondary Education Policy Agency (BKPDM) Number 020 of 2026 concerning the revision of the Learning Outcomes (CP) for Islamic Religious Education and Character Education encourages a pedagogical shift from a memorization-based approach to contextual, meaningful, and character-oriented learning through the five dimensions of love. In the field of Islamic economics, learning has primarily focused on Islamic financial literacy, particularly the distinction between halal and haram transactions, without adequately integrating ecological sustainability, social justice, and intergenerational responsibility. This study aims to formulate the transformation of instructional planning and assessment in Islamic Religious Education, particularly in Islamic economics, toward the paradigm of Sustainable Islamic Education aligned with the 2030 Sustainable Development Goals (SDGs). This research employed a qualitative approach using a library research method through content analysis of the 2026 Learning Outcomes document, Islamic economics literature, and SDGs documents. The findings indicate that instructional planning can be transformed through the formulation of learning objectives based on maqasid al-shariah, the implementation of project-based deep learning, and the integration of SDG indicators into the learning process. Meanwhile, learning assessment should shift toward authentic assessment that evaluates cognitive, affective, and psychomotor domains through fair and sustainable Islamic economic practices. This study proposes a Sustainable Islamic Education framework that integrates literacy, socio-ecological ethics, and sustainable action as a contribution to achieving the 2030 SDGs.